Sildenafil Alleviates Murine Experimental Autoimmune Encephalomyelitis by Triggering Autophagy in the Spinal Cord - Duarte-Silva, Eduardo (2021)
The authors express their gratitude to Oswaldo Cruz Foundation of Pernambuco (FIOCRUZ-PE), Research Excellence Program - Aggeu Magalhães Institute (IAM PROEP#400208/2019-9), Knowledge Generation Program – Oswaldo Cruz Foundation (FIOCRUZ; #VPPCB-007-FIO-18-2-17), The Brazilian National Institute of Science and Technology on Neuroimmunomodulation (INCT-NIM; #465489/2014-1), and Brazilian National Council for Scientific and Technological Development (CNPq; #301777/2012-8) for research support. This study was funded in part by the Coordenação de Aperfeiçoamento de Pessoal de Nıvel Superior - ́Brasil (CAPES) - Finance Code 001. The funders had no role in study design, data collection and analysis, decision to publish, or preparation of the manuscript.